Er-Doped ZnO, CuO and Pentacene Based Broadband Photodetector with High External Quantum Efficiency - Srivastava A.; Jit S.; Tripathi S. (My University, 2025)
This letter reports an Er-doped ZnO (EZO), CuO and Pentacene ternary nanocomposite (NC) thin film based Al/Pentacene:CuO:EZO/PEDOT:PSS/ITO broadband photodetector using low-cost solution method. The NC film shows light absorption in a broad spectral range covering the ultraviolet (UV)-visible-near infrared (NIR) region. The device shows high very external quantum efficiencies (EQEs) of $3.4\times10$ 3, $2.6\times10$ 5 and $2.5\times10$ 5 at 350 nm (UV), 600 nm (visible) and 1050 nm (NIR), respectively, under a reverse bias of -1 V. This high EQE is attributed to trap-assisted charge injection at the NC/Al interface under reverse bias. Characterizations of multiple fabricated devices are used to show repeatability and stability of the proposed photodetector. © 1980-2012 IEEE.